METHODS OF IMPROVEMENT OF PASSPORTATION SYSTEM FUEL AND ENERGY COMPLEX OF UKRAINE - Мітрахович, М. М.; Панченко, Я. М. (Science-based technologies, 2009)
The model of improvement of passportation system as main tool and priority in development energy concervation is considered. It is offered the basic methods of improvement passportation on the basis of revealing wrong of the data in a course of supervision of object. Is established the basic purposes of the power passport and is considered its structure.